Foaming-resistant and scratch-resistant acrylonitrile-butadiene-styrene copolymer material as well as preparation method and application thereof
By using the binding agent of EMA-GMA and POSS-NH2 in ABS materials, the problems of insufficient corrosion and scratch resistance of HFO foaming agent are solved, and the efficient foaming agent and scratch resistance of ABS materials are improved, which is suitable for the application of refrigerator inner liner.
Patent Information
- Application Number
- CN202411708053.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
When existing ABS materials face the erosion of HFO foaming agent, they are prone to damage such as cracks. At the same time, their scratch resistance is insufficient, making it difficult to meet the application needs of refrigerator inner liner.
Ethylene-acrylate-glycidyl methacrylate (EMA-GMA) is used as a cracking resistance agent and is combined with aminolated polysilsesquioxane (POSS-NH2). By reacting the epoxy group on EMA-GMA and the amino group on POSS-NH2, the scratch resistance of the material is improved.
It significantly improves the foaming agent and scratch resistance of ABS materials, ensuring that it can maintain excellent mechanical properties and processing properties for a long time in refrigerator liner applications.
Smart Images

Figure BDA0005154986040000111 
Figure BDA0005154986040000121
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer composite materials and relates to a foaming agent-resistant and scratch-resistant ABS copolymer material and a preparation method and application thereof. Background Art
[0002] ABS is a general engineering plastic with balanced performance in all aspects. It has high mechanical strength, good impact resistance, dimensional stability and good electrical insulation. Among them, sheet-grade ABS shows excellent uniform thinning ability in vacuum forming, and has the advantages of high gloss and good chemical resistance when used as refrigerator liner.
[0003] In the industrial manufacturing of refrigerators, polyurethane foam is usually used to insulate the plastic liner and the outer metal shell. It is worth noting that the foaming agent used for polyurethane foaming often remains in the foam layer, and the long-term use process will corrode the refrigerator liner. So far, different types of ABS compositions have been developed to cope with the erosion of foaming agents such as chlorofluorocarbons (CFCs), hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs) and alkanes, and show good chemical resistance. In recent years, the pressure of global warming has increased, and the environmental protection requirements for foaming agents have become increasingly higher. The new hydrofluoroolefin (HFO) foaming agent has shown great application potential in the field of polyurethane foaming due to its excellent environmental performance and thermal conductivity. However, the erosion of HFO foaming agents on the ABS material of the refrigerator liner is more obvious and more rapid, making the refrigerator liner more prone to damage such as cracks.
[0004] CN 109312134 B discloses an ABS molding composition with improved crack resistance and chemical resistance and its use, which comprises 10 to 35% by weight of ABS graft rubber A obtained by emulsion polymerization, 50 to 75% by weight of SAN copolymer B, 4 to 20% by weight of copolymer C from ethylene and (meth)acrylic acid C1-C6 alkyl ester, and 4 to 20% by weight of ABS graft rubber copolymer D obtained by bulk polymerization. CN 109476895 B also discloses an ABS molding composition with improved crack resistance and chemical resistance and its use, which comprises 10 to 35% by weight of ABS graft rubber A obtained by emulsion polymerization, 50 to 70% by weight of SAN copolymer B, 4 to 20% by weight of elastomeric SBC block copolymer C, and 4 to 20% by weight of ABS graft rubber copolymer D obtained by bulk polymerization. Both patents use HFO foaming agents to improve the environmental stress cracking resistance of ABS compositions. However, the large-scale use of copolymers C and D will greatly damage the strength and modulus of ABS, thereby affecting the blister performance of ABS. At the same time, when used as refrigerator liners, they often collide with various containers, causing scratches on the surface of the liners. Therefore, it is also crucial to improve the scratch resistance of refrigerator liners.
[0005] Therefore, it is necessary to develop a new ABS composition that can resist the erosion of HFO foaming agent while maintaining excellent mechanical properties and processing properties, as well as improving the scratch resistance of the surface, so that it can be successfully used in refrigerator liners. Summary of the invention
[0006] Considering ethylene-acrylate elastomers, crack resistance can be effectively improved; and polysilsesquioxane (POSS) can be added to polymers as rigid particles to significantly improve the hardness of the material, thereby improving the scratch resistance of the material. It is worth noting that POSS has poor compatibility with the polymer matrix and is prone to migration dissipation, thereby reducing scratch resistance. The applicant further discovered that ethylene-acrylate-glycidyl methacrylate (EMA-GMA) containing a large amount of acrylate segments is selected as a crack resistance agent, and amino polysilsesquioxane (POSS-NH2) is selected as a scratch resistance improver. The epoxy group on EMA-GMA reacts with the amino group on POSS-NH2, so that POSS is not prone to migration dissipation, and scratch resistance can be improved for a long time, thereby completing the present invention.
[0007] In order to solve the problems existing in the prior art, the present invention provides a foaming agent resistant and scratch resistant ABS material. The ABS material of the present invention has excellent mechanical strength and good foaming agent resistance and scratch resistance, and the preparation process is simple and easy.
[0008] Another object of the present invention is to provide a preparation method and application of the foaming agent-resistant and scratch-resistant ABS material.
[0009] In order to achieve the above invention object, the technical solution adopted by the present invention is as follows:
[0010] A foaming agent-resistant and scratch-resistant acrylonitrile-butadiene-styrene copolymer (ABS) material is prepared from the following materials:
[0011] 80-95 parts by weight of ABS;
[0012] 5-20 parts by weight of a toughening agent;
[0013] 0-3 parts by weight of processing aids.
[0014] Preferably, the foaming agent-resistant and scratch-resistant acrylonitrile-butadiene-styrene copolymer (ABS) material is prepared from the following materials:
[0015] 80-95 parts by weight of ABS;
[0016] 5-15 parts by weight of a toughening agent;
[0017] 0.1-2 parts by weight of processing aids.
[0018] In the foaming agent-resistant and scratch-resistant ABS material of the present invention, the toughening agent is ethylene-acrylate-glycidyl methacrylate grafted polysilsesquioxane (EMA-GMA-POSS).
[0019] In the present invention, the preparation method of the toughening agent EMA-GMA-POSS is as follows: ethylene-acrylate-methacrylate glycidyl ester (EMA-GMA) and amino polysilsesquioxane (POSS-NH2) are added into a torque mixer at the same time, and after heating and melting and blending for a certain period of time, the toughening agent EMA-GMA-POSS is obtained.
[0020] In the present invention, the heating temperature for melt blending in preparing the toughening agent is 180-200° C., and the mixing time is 5-10 minutes.
[0021] In the foaming agent resistant and scratch resistant ABS material of the present invention, the ABS is prepared by emulsion-bulk SAN blending, or prepared by bulk method, preferably emulsion-bulk SAN blending method ABS; preferably, under the test conditions of 220°C and 10kg, the melt flow index of ABS is 4-40g / 10min, preferably 4-20g / 10min, and more preferably 4-10g / 10min. The higher the melt index of ABS, the better the fluidity of ABS, and the better the fluidity of the composition; however, the higher the melt index of ABS, that is, the lower the molecular weight of ABS, the worse the foaming agent resistance of the composition.
[0022] In the foaming agent and scratch resistant ABS material of the present invention, the processing aid is selected from one or more combinations of antioxidants, lubricants, ultraviolet absorbers, flame retardants, compatibilizers, light stabilizers, heat stabilizers, metal passivators, plasticizers, anti-adhesive agents, colorants, coupling agents, nucleating agents, foaming agents, antibacterial agents, mildew inhibitors, acid scavengers, hydrolysis resistant agents, chain extenders, flow modifiers, matting agents, antistatic agents, reinforcing agents, fillers, antifogging agents, light diffusers, infrared absorbers, fluorescent brighteners and laser marking agents.
[0023] In a preferred embodiment, the processing aid is a combination of an antioxidant, a lubricant and an ultraviolet absorber.
[0024] The antioxidant is one or a combination of two or more of hindered phenols, phosphites, thioesters, benzofurans, acryloyl-modified phenols, and hydroxylamine antioxidants. Preferably, one or more of antioxidants 1076, 1010, 168, and 618 are used.
[0025] The lubricant is one or a combination of two or more of fatty alcohols, metal soaps, fatty acids, fatty acid esters, montanic acid and its derivatives, amide waxes, saturated hydrocarbons, polyolefin waxes and its derivatives, organic silicon and silicone powder, organic fluorine, etc. Preferably, amide wax lubricants are used.
[0026] The ultraviolet absorber is one or a combination of two or more of benzophenone, benzotriazole, triazine, benzoate, cyanoacrylate, and phenylimidazole. Benzotriazole and triazine are preferably used, such as Tinuvin 234, Tinuvin 360, Tinuvin 1577, etc. from BASF.
[0027] The other additives mentioned above can be selected conventionally in the art without any special limitation, and those skilled in the art can make conventional selections according to the processing performance requirements. The foaming agent-resistant and scratch-resistant ABS material of the present invention can selectively use the above additives according to the product performance characteristics.
[0028] On the other hand, the present invention also provides a method for preparing the above-mentioned foaming agent-resistant and scratch-resistant ABS material, the method comprising the following steps:
[0029] (1) Premixing: ABS, toughening agent (EMA-GMA-POSS) and optional processing aids are mixed according to proportion to obtain a premix;
[0030] (2) Extrusion: The obtained premix is melt-blended, granulated and dried by an extruder to obtain foaming agent-resistant and scratch-resistant ABS material pellets.
[0031] Preferably, the extruder in step (2) is preferably a twin-screw extruder, the processing temperature zone of the twin-screw extruder is 200-220° C., the screw speed is 300-800 rpm, and the vacuum degree is between -0.9 bar and -0.5 bar.
[0032] In another aspect of the present invention, the aforementioned foaming agent resistant and scratch resistant acrylonitrile-butadiene-styrene copolymer material or the foaming agent resistant and scratch resistant acrylonitrile-butadiene-styrene copolymer material prepared by the aforementioned preparation method is used in a refrigerator liner.
[0033] Compared with the prior art, the present invention has the following positive effects:
[0034] The ABS material of the present invention contains a large amount of ethylene-acrylate-glycidyl methacrylate (EMA-GMA) containing acrylic acid ester segments, which can be used as an anti-cracking agent to effectively improve the foaming agent resistance, and the amino polysilsesquioxane (POSS-NH2) can effectively improve the scratch resistance; and the epoxy group on EMA-GMA reacts with the amino group on POSS-NH2, so that POSS is not easy to migrate and dissipate, and the scratch resistance can be improved for a long time. DETAILED DESCRIPTION
[0035] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In the event of ambiguity, the present specification including definitions will prevail.
[0036] Unless otherwise indicated, all parts, ratios, etc. are by weight.
[0037] The term "at least one" as used herein means that the aforementioned elements may be used alone or in combination of one or more.
[0038] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper numerical limit and a preferred lower numerical limit, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical ranges listed herein are intended to include the endpoints of the range, and all integers and fractions within the range. For example, "1-8" covers 1, 2, 3, 4, 5, 6, 7, 8 and any sub-range consisting of any two values therein, such as 2-6, 3-5.
[0039] The scheme of the present invention is further described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are merely examples for clearly illustrating the technical scheme of the present invention, and are not intended to limit the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the scope of protection created by the present invention.
[0040] The present invention is described in detail below.
[0041] The performance test is as follows:
[0042] Tensile properties were tested according to ASTM D638.
[0043] Foaming agent resistance test: a tensile specimen under 0.5% strain was completely immersed in trans-1-chloro-3,3,3-trifluoropropene (LBA), placed in a 0°C refrigerator, and taken out after 48 hours to test the change in tensile strength.
[0044] Scratch resistance: △E, Volkswagen standard PV3952
[0045] The ingredients of the comparative examples and embodiments are as follows:
[0046] ABS: ABS produced by emulsion-bulk SAN blending method, melt flow index is 5g / 10min (220℃, 10kg), Zhenjiang Chimei Company;
[0047] Ethylene-acrylate-glycidyl methacrylate: brand AX8900, Arcoma, France;
[0048] Amination polysilsesquioxane: cage polysilsesquioxane-octaammonium (amino), Xi'an Qiyue Biotechnology Co., Ltd.;
[0049] Antioxidant: Irganox B900, produced by BASF;
[0050] Lubricant: EBS, produced by CMS Indonesia.
[0051] Preparation of toughening agent EMA-GMA-POSS-1: After the temperature of the internal mixer rises to 190°C, 95 parts of EMA-GMA and 5 parts of POSS-NH2 are added to the internal mixer at the same time. After heating and melt blending for 5 minutes, the product modified toughening agent EMA-GMA-POSS-1 is obtained.
[0052] Preparation of toughening agent EMA-GMA-POSS-2: After the temperature of the internal mixer rises to 190°C, 90 parts of EMA-GMA and 10 parts of POSS-NH2 are added to the internal mixer at the same time. After heating and melt blending for 5 minutes, the product modified toughening agent EMA-GMA-POSS-2 is obtained.
[0053] Preparation of toughening agent EMA-GMA-POSS-3: After the temperature of the internal mixer rises to 190°C, 85 parts of EMA-GMA and 15 parts of POSS-NH2 are added to the internal mixer at the same time. After heating and melt blending for 5 minutes, the product modified toughening agent EMA-GMA-POSS-3 is obtained.
[0054] Preparation of toughening agent EMA-GMA-POSS-4: After the temperature of the internal mixer rises to 190°C, 80 parts of EMA-GMA and 20 parts of POSS-NH2 are added to the internal mixer at the same time. After heating and melt blending for 5 minutes, the product modified toughening agent EMA-GMA-POSS-4 is obtained.
[0055] Preparation of toughening agent EMA-GMA-POSS-5: After the temperature of the internal mixer rises to 190°C, 75 parts of EMA-GMA and 25 parts of POSS-NH2 are added to the internal mixer at the same time. After heating and melt blending for 5 minutes, the product modified toughening agent EMA-GMA-POSS-5 is obtained.
[0056] Example 1
[0057] The material composition includes the following raw materials in weight ratio: ABS: 95 parts, EMA-GMA-POSS-1: 5 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation is completed, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0058] Example 2
[0059] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, EMA-GMA-POSS-1: 10 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation is completed, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0060] Example 3
[0061] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, EMA-GMA-POSS-2: 10 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation is completed, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0062] Example 4
[0063] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, EMA-GMA-POSS-3: 10 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation is completed, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0064] Example 5
[0065] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, EMA-GMA-POSS-4: 10 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation is completed, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0066] Example 6
[0067] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, EMA-GMA-POSS-5: 10 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation is completed, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0068] Comparative Example 1
[0069] The material composition comprises the following weight ratios: 100 parts of raw material ABS, 0.3 parts of antioxidant, and 0.3 parts of lubricant. The material composition is added to a high-speed mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, and after granulation, it is dried at 80°C for 4 hours to fully remove moisture, and the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0070] Comparative Example 2
[0071] The material composition includes the following weight ratio of raw materials: ABS 92.5 parts, EMA-GMA 7.5 parts, antioxidant 0.3 parts, lubricant 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0072] Comparative Example 3
[0073] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, EMA-GMA: 10 parts, antioxidant: 0.3 parts, lubricant: 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0074] Comparative Example 4
[0075] The material composition includes the following raw materials in weight ratio: ABS: 90 parts, POSS-NH2: 10 parts, antioxidant: 0.3 parts, lubricant: 0.3 parts. The material composition is added to a high mixer for mixing, added to a twin-screw extruder, extruded into granules, the processing temperature is 210°C, the screw speed is 400rpm, the vacuum degree of the vacuum device of the twin-screw metering section is within -0.7 bar, after granulation, it is dried at 80°C for 4h to fully remove moisture, the injection mold temperature is controlled at 50°C, the barrel temperature is 210°C, the injection speed is 50mm / s, and the injection pressure is 60bar to obtain standard specimens and sample plates.
[0076] Comparison of material properties between the embodiment and the comparative example:
[0077]
[0078]
[0079] It can be seen from the embodiments and comparative examples that the epoxy group on EMA-GMA and the amino group on POSS-NH2 react to act as a toughening agent (EMA-GMA-POSS), so that POSS is less likely to migrate and dissipate, the scratch resistance can be improved for a long time, and the foaming agent resistance and scratch resistance of the material can be effectively improved, so that it can be successfully used to manufacture refrigerator liners.
[0080] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to allow professionals who understand such technologies to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the essential contents of the present invention should be included in the protection scope of the present invention.
Claims
1. A foaming agent-resistant and scratch-resistant acrylonitrile-butadiene-styrene copolymer material, characterized in that: Made from the following materials: 80-95 parts by weight of ABS; 5-20 parts by weight of a toughening agent; 0-3 parts by weight of processing aids.
2. The copolymer material according to claim 1, characterized in that Made from the following materials: 80-95 parts by weight of ABS; 5-15 parts by weight of a toughening agent; 0.1-2 parts by weight of processing aids.
3. The copolymer material according to claim 1 or 2, characterized in that: The toughening agent is ethylene-acrylate-glycidyl methacrylate grafted polysilsesquioxane (EMA-GMA-POSS); Preferably, the preparation process of the EMA-GMA-POSS is as follows: Ethylene-acrylate-glycidyl methacrylate (EMA-GMA) and amino-polysilsesquioxane (POSS-NH2) are added into a torque mixer for melt blending to obtain the toughening agent EMA-GMA-POSS.
4. The copolymer material according to claim 3, characterized in that The heating temperature for melt blending is 180-200°C and the mixing time is 5-10 minutes.
5. The copolymer material according to claim 3, characterized in that: The ABS is ABS prepared by an emulsion-bulk SAN blending method or a bulk method, preferably ABS by an emulsion-bulk SAN blending method.
6. The copolymer material according to claim 5, characterized in that When the test conditions are 220° C. and 10 kg, the melt flow index of ABS is 4-40 g / 10 min, preferably 4-20 g / 10 min, and more preferably 4-10 g / 10 min.
7. The copolymer material according to claim 3, characterized in that: The processing aid is selected from at least one of antioxidants, lubricants, ultraviolet absorbers, flame retardants, compatibilizers, light stabilizers, heat stabilizers, metal passivators, plasticizers, anti-sticking agents, colorants, coupling agents, nucleating agents, foaming agents, antibacterial agents, mildew inhibitors, acid scavengers, hydrolysis resistant agents, chain extenders, flow modifiers, matting agents, antistatic agents, reinforcing agents, fillers, anti-fogging agents, light diffusers, infrared absorbers, fluorescent brighteners, and laser marking agents.
8. The copolymer material according to claim 7, characterized in that The processing aid is a combination of an antioxidant, a lubricant and an ultraviolet absorber; Preferably, the antioxidant is one or a combination of two or more of hindered phenols, phosphites, thioesters, benzofurans, acryl-modified phenols, and hydroxylamine antioxidants; Preferably, the lubricant is one or a combination of two or more of fatty alcohols, metal soaps, fatty acids, fatty acid esters, montanic acid and its derivatives, amide waxes, saturated hydrocarbons, polyolefin waxes and its derivatives, silicones and silicone powders, and organic fluorines, preferably amide waxes; Preferably, the ultraviolet absorber is one or a combination of two or more of benzophenone, benzotriazole, triazine, benzoate, cyanoacrylate, and phenylimidazole; preferably, benzotriazole and triazine are used.
9. The method for preparing the foaming agent-resistant and scratch-resistant acrylonitrile-butadiene-styrene copolymer material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Premixing: ABS, toughening agent (EMA-GMA-POSS) and optional processing aids are added into a mixer according to proportion and stirred to obtain a premix; (2) Extrusion: melt-blending, granulating and drying the obtained premix by a twin-screw extruder to obtain ABS material pellets that are resistant to foaming agents and scratches; Preferably, in step (2), the temperature of the processing zone of the twin-screw extruder is controlled at 200-220° C., the screw speed is controlled at 300-800 rpm, and the vacuum degree of the vacuum pump of the twin-screw metering section is controlled at between -0.9 bar and -0.5 bar.
10. Use of the foaming agent resistant and scratch resistant acrylonitrile-butadiene-styrene copolymer material according to any one of claims 1 to 8 or the foaming agent resistant and scratch resistant acrylonitrile-butadiene-styrene copolymer material prepared by the preparation method according to claim 9 in refrigerator liner.
Citation Information
Patent Citations
ABS molding compositions with improved crack resistance and chemical resistance and their applications
CN109312134B
ABS molding compositions with improved crack resistance and chemical resistance and their applications
CN109476895B
High weather resistance polycarbonate / acrylonitrile-butadiene-styrene (PC / ABS) alloy composition and preparation method thereof
CN102719077A
Spraying-free high-weather-resistant scratch-resistant halogen-free flame-retardant ABS (acrylonitrile butadiene styrene) preparation and process
CN104448673A
ABS composite material for low-odor low-volatilization scraping resistant automobile trim and preparation method
CN105566834A